Two decades of pharmacovigilance and clinical experience with highly purified rabies immunoglobulin F(ab')2 fragments - Elisa Reveneau; Pascale Cottin; Anvar Rasuli (Expert Review of Vaccines, 2017)
Introduction: Rabies is a worldwide zoonotic viral disease with no specific treatment once symptoms occur; manifest disease is almost always fatal. WHO recommendations for exposed individuals include immediate attention to the wound and use of rabies immunoglobulin and/or vaccine for post-exposure prophylaxis (PEP). Here, we provide an overview of the clinical experience with a highly purified preparation of F(ab’)2 fragments from equine rabies immunoglobulin (F(ab’)2 pERIG; FavirabTM) in rabies PEP. Areas covered: Our review comprises a retrospective analysis of adverse event reports in the Sanofi Pasteur global pharmacovigilance database for F(ab’)2 pERIG, including adverse event reports from eight Sanofi Pasteur-sponsored clinical trials and post-market surveillance data collected between 1995 and 2014. The general safety profile of F(ab’)2 pERIG is discussed, as are the occurrence of rare anaphylactic reactions, and suspected intervention failure. Expert commentary: Over 20 years of clinical development and post-licensure experience has established the safety and effectiveness of F(ab’)2 pERIG (FavirabTM) in rabies PEP.